Interacting, sharing and bonding: 'notes of personal experience' by 19th century women travellers - Irene Kamberidou (Gender, Place & Culture: A Journal of Feminist Geography, 2015)
Full text:  http://www.tandfonline.com/eprint/QfxxQ5f9E7wVHtXDu7kB/full To cite this article: Irene Kamberidou (2015): Interacting, sharing and bonding: ‘notes of personal experience’ by nineteenth-century women travellers, Gender, Place & Culture: A Journal of Feminist Geography, DOI: 10.1080/0966369X.2015.1013451  To link to this article: http://dx.doi.org/10.1080/0966369X.2015.1013451